Anthropology and the AlDub nation entertainment as politics and politics as entertainment - Pertierra, Raul (Philippine Studies: Historical and Ethnographic Viewpoints, 2016)
The links between politics and entertainment in the Philippines are well known, but few have noted these links in the media phenomenon known as AlDub. As a subpart of Eat Bulaga, a long-standing midday TV show, AlDub has gained a life of its own, giving its actors national and even global prominence. How was this possible? Was it happenstance or do basic interests and structures explain its popularity? A deep ethnographic account of how popular culture is generated, reproduced, and consumed reveals its anchoring in material structures the interests of which are often disguised or unacknowledged. Anthropology provides a way of exploring such interests and structures.